Gamma diversity: derived from and a determinant of alpha diversity and beta diversity. An analysis of three tropical landscapes - Lucrecia Arellano; Gonzalo Halffter (Acta Zoológica Mexicana, 2003)
Using three taxonomic groups of beetles we examine how alpha and beta diversity influence the species richness of a landscape (gamma diversity), and vice versa. That is, how the species richness of a landscape ? which is a historical and biogeographical phenomenon ? contributes to the values of alpha diversity (1) at a given site, (2) in a community, (3) in terms of cumulative species richness by community, and also contributes to (4) the intensity of species exchange between communities. To explore this question, we used two subfamilies of Scarabaeoidea: Scarabaeinae and Geotrupinae, and the family Silphidae. In all analyses these three taxonomic groups are considered as a single indicator group: the copronecrophagous beetles. Information is also included on the subfamily Aphodiinae (Scarabaeoidea), coprophagous beetles not included in the indicator group. Several types of vegetation located in three landscapes (tropical, transition and mountain) were studied, and these are located along an altitudinal gradient in the central part of the state of Veracruz, Mexico. We base this study on the following concepts. The alpha diversity of an indicator group reflects the number of species that use a given environment or resource in a given place or community. Spacial beta diversity is related to the response of organisms to spatial heterogeneity. Gamma diversity depends primarily on the historical and geographic processes that operate on the mesoscale level and is also affected by alpha and beta diversity. It is on this scale of landscape that human actions, such as the modification and fragmentation of vegetation, have their most important effects. These are, however, often beyond the scope of ecological analyses carried out on a local scale. In the three landscapes, sampling was carried out regularly at 67 sites, with complementary sampling at another 69 sites. Twenty-six types of vegetation communities were studied. A total of 16,152 specimens representing 60 species were captured (52 species of Scarabaeinae, 4 Geotrupinae and 4 Silphidae). In the tropical landscape the community richest in species was low deciduous forest. In the transition landscape, cloud forest was the richest. Each of these communities is the most representative of their respective altitudinal bands. In contrast, the greatest species richness in the mountain landscape occurred in the mountain grasslands and pastures; types of community favoured by or even created by human intervention. This is explained by the expansion of heliophilous species from the Mexican High Plateau into these areas. In the tropical landscape the species richness of the pastures is similar to that of its forests, but with a partially different composition which is characterized by the dominance of heliophilous and coprophagous species; the latter, in addition to the more ubiquitous species that are shared with the tropical forest. In the transition landscape the cloud forest and the coffee plantations with polyspecific shade are important in the context of conserving the fauna. This type of community offers arboreal cover and occupies the majority of this landscape, allowing the groups of insects studied to move between remnant fragments of cloud forest. On the landscape scale but not locally, the fragmentation of natural communities does not appear to have reduced the number of species for the beetles of the indicator group. In each landscape disturbance by human activity appears to have been overcome for distinct reasons. In the tropical landscape we find the heliophilous beetle fauna characteristic of pastures, and this has increased by two species of recent invaders. In the transition landscape, the coffee plantations with polyspecific shade create a communication matrix, while in the mountain landscape the expansion of the mountain pastures has made conditions more favourable for heliophilous species. These results are not necessarily expected for other groups of organisms.